(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The stomach is the most common site of gastrointestinal stromal tumours representing 50% to 70%. Gastric GISTs are usually asymptomatic, discovered incidentally during endoscopic or radiological investigation. Feasibility and long-term safety of laparoscopic removal of gastric GISTs of the stomach is well established for lesions smaller than 3cm. We report a case of giant gastric GIST of size more than 10cm resected laparoscopically without any tumour rupture.